Walking Characteristics and Bone Mineral Density in Community-dwelling Elderly Women: A Cross-Sectional Study - KOMATSU, Taiki; PARK, Hyuntae; PARK, Sungjin; KAMINAI, Tetsuo; MUTOH, Yoshiteru (Journal of Physical Education and Medicine, 2003)
In this cross-sectional study we investigated the association of walking characteristics with bone mineral density (BMD) in elderly women to examine the relationships between mobility, balance, body sway, and osteoporosis. Participants were 109 elderly Japanese women aged 62-89 years, ambulatory and voluntarily enrolled in the Fall Prevention Program. For each participant, bone mineral density in the femur and speed of sound, transmission index and osteo-sono index (OSI) in the calcaneus were estimated using a dual-energy x-ray absorptiometry (DEXA) and quantitative ultrasound (QUS) instrument, and they were grouped (osteoporosis, osteopenia, or normal) according to their BMD level. Measurements were performed in the right femur and heel. We also examined waist girth, hip girth, 10-m walking speed, maximal step length, 40-cm step, one-legged balance time with eyes open, and postural sway. There were no significant differences in 40-cm step, body sway, and one-legged balance time among the groups. In contrast, maximal step length, 10-m walking speed, total step during the 10m walk, and mean stride length during the 10-m walk were significantly associated with the higher BMD group (normal)(p<0.05). There were significant correlations between walking test parameters and femoral neck BMD (10-m walking speed: r=-0.23, total step: r=-0.24, mean stride length: r=0.24, maximal step length: r=0.19) and OSI (10-m walking speed: r=0.25, total step during 10-m walk: r=-0.18, mean stride length during 10-m walk: r=0.19, maximal step length: r=0.31). Our results suggest that short maximal step length and slow 10-m walking speed are impaired with osteoporosis in elderly women. Femoral neck BMD and calcaneual OSI are correlated with these mobility parameters. Thus, the characteristics of this simple walker's test could be a useful instrument in the diagnosis of osteoporotic women.